PENGEMBANGAN MODEL PEMBELAJARAN INTERAKTIF BERBASIS E-LEARNING PADA MATAKULIAH DISAIN INSTRUKSIONAL - Sahat Siagian; Binsar Panjaitan; Yasaratodo Wau (LPPM Universitas Negeri Medan, 2016)
This research aims to develop a model of Interactive Learning-based elearning-assisted program Edmodo on Subject of Design Instructional, this research is expected to produce (1) Generate Model Interactive Learning Based eLearning proper use, easy to learn and can be used for individual learning and learning material that refers to competencies that have been established, (2) To know the results of the implementation of Model Interactive learning Based elearning subject on the design of instructional as well as the right strategies used in learning design instructional, (3) To determine the effectiveness of Model Interactive learning Based e-learning subject of developed in instructional design and to determine the model of interactive learning that is effective and efficient. This research was conducted three stages. In the first stage in the first year to do an analysis of the interactive learning model that is most appropriate to use in learning instructional design, through a survey of preliminary studies, including the identification of learning needs and determine the competency standards subjects, analysis of learning. Identified characteristic and early behavior of students, basic competence and indicator writing, writing reference benchmark tests, preparing instructional strategies, develop learning materials. Then proceed with the initial design manufacture moodel based learning, instructional design based e-learning, and develop story board.